2014
DOI: 10.1096/fj.14-254110
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and unique nucleolar microenvironment revealed by fluorescence correlation spectroscopy

Abstract: Organization and functions of the nucleolus is maintained by mobilities and interactions of nucleolar factors. Because the nucleolus is a densely packed structure, molecular crowding effects determined by the molecular concentrations and mobilities in the nucleolus should also be important for regulating nucleolar organization and functions. However, such molecular property of nucleolar organization is not fully understood. To understand the biophysical property of nucleolar organization, the diffusional behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 48 publications
(202 reference statements)
10
48
0
Order By: Relevance
“…More specifically, the study of protein dynamics in the nucleus can be relevant for understanding many nuclear processes and for characterizing the complex nuclear architecture 1 3 . For instance, by using biologically inert macromolecules and measuring their mobility, it is possible to gather insights about the chromatin architecture at a scale comparable to the size of the macromolecules 3 5 . For these reasons many techniques have been applied over the years for studying protein diffusion in the nuclear environment 6 11 .…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the study of protein dynamics in the nucleus can be relevant for understanding many nuclear processes and for characterizing the complex nuclear architecture 1 3 . For instance, by using biologically inert macromolecules and measuring their mobility, it is possible to gather insights about the chromatin architecture at a scale comparable to the size of the macromolecules 3 5 . For these reasons many techniques have been applied over the years for studying protein diffusion in the nuclear environment 6 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The study of protein dynamics and the use of EGFP as a probe for investigating the structure of cellular compartments have been used for decades 1,2,4,6,11,13,33,34 while, on a parallel effort, many microscopy techniques have been developed from the super-resolution imaging field (STED, ISM…) and from the fluorescence fluctuations field (pCF, iMSD, spot-variation FCS, N&B…) in order to provide increased spatiotemporal resolution to address dynamic as well as structural information of the cellular environment. Although many studies have focused on the coupling of STED with fluorescence fluctuation techniques, our work is, at the best of our knowledge, the first coupling ISM concepts to such techniques enabling, on a different spatial scale, the super-resolution investigation of many dynamic properties in a single analysis in a few seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the D value in DM cell cultured by hypertonic media showed much smaller than the theoretical value. Since hypertonic stress enforces molecular crowding in the cellular components due to the osmotic extraction of water from the cells (Richter et al, 2007), these results suggest that molecular diffusion in the cytosol and chromosome at high osmolality is largely affected by molecular crowding induced by the hypertonic conditions (Golkaram et al, 2016;Park et al, 2015).…”
Section: Relationship Between Chromosomal Ri and Diffusion Of Intrachmentioning
confidence: 95%
“…While it remains unclear how protein factors find and interact with their targets, the structure and function of cellular bodies are likely maintained by mobility and interaction with related factors during the cell cycle. Previous studies using biophysical methods such as fluorescence correlation spectroscopy (FCS) demonstrated that various probe molecules freely diffuse in the nucleus and various subnuclear bodies, such as chromatin, chromosomes, and nucleoli (Hihara et al, 2012;Pack et al, 2006;Park et al, 2015;Wachsmuth et al, 2008). FCS based on confocal laser scanning microscopy (CLSM) was applied as a useful and highly sensitive technique for quantitatively assessing molecular concentration and diffusion of fluorescent probe in aqueous solutions and living cells (Eigen and Rigler, 1994;Erdel et al, 2011;Magde et al, 1974;Pack et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation